The Possible Role of a Meta-Religious Symbology in the Conversion of the Batak of North Sumatra - MAHMUD LAYAN HUTASUHUT (BAHAS, 2013)
Underlying metaphysical doctrines and value systems upon which various religions are constructed, tribal or otherwise, act as primary pathways upon which religious conversion takes place. In other words, the initiate must recognize an underlying truth within the new sign system from the established system of signs comprising their own value paradigm, that is known as culture. The focus of this study is the Batak people of North Sumatra, Indonesia. Formally, perhaps the only cannibalistic tribe having its own system of writing and divination, the Batak resisted conversion to Islam by Acehnese to the north for several hundred years, yet many were converted to Christianity quite willingly during the 19th century. This marked the beginning of a conversion process still going on to this day. Today, most of the approximately 1.5 million Batak are either Catholic or Protestant. There are, however, still many who maintain practices from the old religion, adat, as well as a minority particularly in the southern Batak lands who have converted to Islam either from Christianity or from the original animist religion. Such conversions and shifts between religious and cultural paradigms still occur quite frequently in the region to this day. Therefore, the Batak region is an ideal place to study the inherent metaphysical mechanisms involved in the process of such paradigm shifts and conversion. Furthermore, in all Batak regions, elements of the adat are maintained simultaneously with the newer monotheistic religions. Key Words : meta-religious symbology, religious and cultural paradigms